Mechanistic Insight and Inhibitory Potential of Fluvastatin-Derivatives against Dyslipidemia - Mahzari, Ali; Khalifa, Eman H.; Zaeri, Ali A; Alyahyawi, Hanan E; Alwanian, Wanian M; Wali, Saad M.; Almuzaini, Ohood; Alshuweishi, Yazeed (International Journal of Pharmaceutical Investigation, 2025)
Background Cardiovascular diseases comprehend a array of situations that disturb the heart and blood vessels, making them a principal cause of morbidity and mortality worldwide. Dyslipidemia, an imbalance in lipids, such as cholesterol, Low-Density Lipoprotein Cholesterol (LDL-C), triglycerides and High-Density Lipoprotein (HDL), is a significant risk factor for cardiovascular disease and contributes to numerous deaths annually. The development of cholesterol-degrading drugs, known as statins, began in the mid-1970s and their effects on intracellular processes have been well documented. Materials and Methods Fluvastatin, a statin widely used in cardiovascular disease, inhibits hydroxymethyl glutaryl-coenzyme A, a vital enzyme in cholesterol biosynthesis. This study aimed to discover new therapeutic drugs to prevent cardiovascular diseases by deriving new compounds from fluvastatin. Results The investigation involved several processes including derivative generation, molecular docking, ADME analysis, PASS prediction, rodent toxicity assessment and identification of possible adverse effects. After evaluating a vast dataset of 194 derivatives, compounds that met stringent criteria across all parameters were selected. Conclusion Two promising compounds from this filtered set were further assessed through Molecular Dynamics (MD) simulation and Principal Component Analysis (PCA), along with the control.
Keywords: Cholesterol; CVDs; Drug designing; Dyslipidemia; MD simulation; Molecular docking; PCA